ANALISIS PERHITUNGAN, PEMUNGUTAN, DAN EFEKTIVITAS PAJAK HOTEL DAN PAJAK RESTORAN SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH - CHRISTIAN CHRISTIAN; LIE PIEN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
Hotel tax and restaurant tax is the one of the sources of income from regional tax. The purpose of this research is to determine the calculation, collections and effectiveness of hotel tax and restaurant tas and its contribution to local region income of Bekasi city period 2014-2016. The reasearch method used in this reasearch is descriptive analysis method. The secondary data in this study were obtained from BAPENDA Bekasi City. Data that has been used in this research is organizational structure, number of hotel taxpayers and number of rastaurant taxpayers, number of local tax letter, sample taxes, targets & realization hotel tax and restaurant tax, targets & realizations of local revenue and interviews.The result of this research showed that the process of calculation and collection by BAPENDA Bekasi Cityis in accordance with the regional regulation Bekasi City Number 14 of 2011 and the regional regulation Bekasi City Number 08 of 2011. The effectiveness of hotel tax receipts and restaurant taxes are very effective. The contribution of hotel tax is categorized as very low and restaurant taxes are categorized less than the original income of Bekasi City